The Dual Role of Kinin/Kinin Receptors System in Alzheimer’s Disease - Ji, Bingyuan; Wang, Qinqin; Xue, Qingjie; Li, Wenfu; Li, Xuezhi; Wu, Yili (Frontiers in Molecular Neuroscience, 2019)
Alzheimer’s disease (AD) is the most common neurodegenerative disease characterized by progressive spatial disorientation, learning and memory deﬁcits, responsible for 60-80% of all dementias. However, the pathological mechanism of AD remains unknown. Numerous studies revealed that kinin/kinin receptors system (KKS) may be involved in the pathophysiology of AD. In this review, we summarized the roles of KKS in neuroinflammation, cerebrovascular impairment, tau phosphorylation, and amyloid beta (Aβ) generation in AD. Moreover, we provide new insights into the mechanistic link between KKS and AD, and highlight the KKS as a potential therapeutic target for AD treatment.